Housing Liabilities and Inadequate Housing Conditions in Brazilian Municipalities: Subnormal Agglomerates and the Challenges of the 2030 Agenda - Ribeiro Mello, Andrea Justino (2024)
This article addresses the issue of housing and subnormal agglomerations in selected municipalities within the Metropolitan Region of Rio de Janeiro, Brazil, and verifies the feasibility of achieving target 11.1 of the Sustainable Development Goals (SDGs) on a regional scale. Recent studies commissioned and released by the Brazilian Federal Government and Census data are used as data sources. In the reality studied, the municipality of Belford Roxo, with alarming rates of communities and households in the context of subnormal agglomerations, shows a tendency to deteriorate the housing situation. Japeri and Queimados, due to the demographic growth rates of recent decades. Conversely, Nova Iguaçu, Mesquita, and Nilópolis, with smaller proportions of their populations living in subnormal agglomerations, present a favorable condition for achieving target 11.1 of the SDGs by 2030.